THU0647-HPR SHARED DECISION MAKING AMONGST RHEUMATOLOGISTS IN TRAINING IN THE NETHERLANDS: WHERE DO WE STAND?. (2nd June 2020) - Kranenburg, L.; Dankbaar, M.; Basoski, N.; Van den Broek, W.; Hazes, J.
Abstract : Background: The training curriculum for rheumatologists in training in the Netherlands describes competences and entrusted professional activities (EPA) to monitor the progress in learning. However, this training program does not discuss training of Shared Decision Making. As the basis for shared care and patient participation is made during these years, the question arises how rheumatologist in training think about Shared Decision Making and how they use this in daily practice. Objectives: Inventory of vision, experience and self-evaluation of skills related to Shared Decision Making amongst rheumatologists in training in the Netherlands in order to identify barriers in the implementation of Shared Decision Making in daily practice. Methods: Qualitative data was collected from on online survey amongst rheumatologists in training who were registered in January 2018 by the Dutch Society of Rheumatology. Results: Forty-two rheumatologists in training from various years of training responded (60%). Respondents think that Shared Decision Making is important. A third applies Shared Decision Making on a regular basis in daily practice. Self rating of skills for Shared Decision Making varies from sufficient to good. However, respondents are uncertain about their performance due to a lack of feedback and unclearness of the concept. They indicate that Shared Decision Making is not possible for all patients and find it difficult to assess whether the patient has a clear understanding of the options. Patient's preferences are discussed only by 33% of the doctors on a regular basis when starting new treatment. Conclusion: Rheumatologists in training agree on the importance of Shared Decision Making, but are uncertain about their performance. Unclearness of the concept is described as a known barrier in literature 1, 2 and is frequently mentioned by respondents. Rheumatologist in training indicate that not all patients are fit for Shared Decision Making. Regarding the limited training on the subject this could also be a misjudgment of patients preferences and lack of experience how to deal with different patient types. There is a clear plea for more training and feedback on the subject. Training should be integrated in the curriculum focusing on how to assess patients preferences and how to apply Shared Decision Making also for patients who indicate to leave decisions up to their doctor. References: [1]van Veenendaal, H. et al. Accelerating implementation of shared decision-making in the Netherlands: An exploratory investigation. Patient Educ Couns 101, 2097-2104 (2018). [2]Legare, F., Ratte, S., Gravel, K. & Graham, I. D. Barriers and facilitators to implementing shared decision-making in clinical practice: update of a systematic review of health professionals' perceptions. Patient Educ Couns 73, 526-535 (2008). Disclosure of Interests: Laura Kranenburg Grant/research support from: Pfizer and UCB for the development of the Reuma App, a tool to support selfmanagement for patients. This is not used for the research related to the submitted abstract., Mary Dankbaar: None declared, Natalja Basoski: None declared, Walter Van den Broek: None declared, Johanna Hazes: None declared